An economic analysis of higher education financing policies - Sánchez, Juan Matías (2004)
This paper develops a model in which it is possible to evaluate alternatives of higher education financing. The alternative systems under discussion are: total fecing, graduates' taxes and uniform taxes (this can be associated to the scheme presently used in the Argentina to finance the universities). Assessment of the alternatives is performed over welfare, based on the indicators of poverty, equality, and the average levels of utility and wealth. Likewise, the functions of welfare presented by Bentham, Rawls, Atkinson, Sen and Kakwani are also considered. The most remarkable results are obtained through the simulation of an economy under two scenarios. In that way, the system of graduates' taxation is found to be better for welfare; whereas the system of uniform taxation only can be justified as it maximizes the number of students.